Food Caught in the Sanctions War: is Food Security a Casualty? - Elena Vasilievna Zhiryaeva (Управленческое консультирование)
This article examines changes in food security conditions in Russia following the introduction of general and commodity-specific embargo. While the physical availability of food increased with growth in agricultural production, the effect was offset by a decline in imports. Consumer prices rose due to reduced economic availability of meat and milk. Food insecurity in Russia is caused by increasing prices. There is no import dependence as measured by the division of food import by a total merchandise export. We have discovered that increasing food prices in the Russian Federation during the 2013-2015 periods affected not only products placed under embargo, but as much other commodity groups. Embargos were imposed on goods whose prices were less likely to rise. At the same time, similar food produced in Russia was not competitive on the world market. Therefore, import substitution of this kind necessarily led to decline in the quality of food and a reduction of food security. In our opinion, fish and apples aren’t a suitable object for sanctions unlike some other goods such as eggs or flour.